LINC00511/miRNA-143-3p Modulates Apoptosis and Malignant Phenotype of Bladder Carcinoma Cells via PCMT1 - Dong, Li-Ming; Zhang, Xi-Ling; Mao, Ming-Huan; Li, Yan-Pei; Zhang, Xi-Yan; Xue, Dong-Wei; Liu, Yi-Li (Frontiers in Cell and Developmental Biology, 2021)
Bladder cancer has easy recurrence characteristics, but its occurrence and development mechanism is still unclear. Non-coding RNA is a kind of RNA that exists widely and cannot be translated into proteins, which has plays a key role in the regulation of biological functions of tumor cells. However, the regulation mechanism of non-coding RNA on bladder tumors is not fully understood. By microarray analysis and database analysis, we found that LINC00511 was significantly highly expressed in bladder cancer. The expressions of LINC00511, miR-143-3p and PCMT in bladder cancer tissues and cells were detected by qRT-PCR. The relationship between the expressions of miR-143-3p and PCMT1 and the clinicopathological parameters of the tumor was analyzed. The proliferation and invasion of bladder cancer cells were detected by MTT assay and transwell assay. The expression levels of E-cadherin and Vimentin in bladder cancer cells were detected by western blot. Cell apoptosis were detected by flow cytometry. In vivo, TCCSUP or SW780 cells were inoculated into BALB/c nude mice to detect tumor volume and weight. Bioinformatics and dual luciferase reporter gene were used to analyze the relationship between LINC00511 and miR-143-3p and its downstream target gene PCMT1. The results showed that LINC00511 could target miR-143-3p/PCMT1 to regulate the proliferation, migration and apoptosis of bladder cancer TCCSUP or SW780 cells, and promote the occurrence and development of bladder cancer.